2019
DOI: 10.1080/13696998.2019.1669329
|View full text |Cite
|
Sign up to set email alerts
|

Primary immune thrombocytopenia in US clinical practice: incidence and healthcare burden in first 12 months following diagnosis

Abstract: Introduction: Primary immune thrombocytopenia (ITP), an autoimmune disorder characterized by low platelet count, can lead to serious bleeding events. Little is known about the current epidemiology of ITP in the US, and even less is known about the current healthcare burden of ITP, especially in the 12-month period following ITP diagnosis. Method: We used a retrospective cohort design and data from two US private healthcare claims databases (2010)(2011)(2012)(2013)(2014)(2015)(2016) to identify persons with evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…Recent estimates from US health care claims databases (2010-2016) found an annual incidence of ITP of 6.1 per 100 000 people. 1 New ITP diagnoses occur in nearly 20 000 children and adults each year in the United States, with collective medical care costs of more than $400 million within the first 12 months after diagnosis. 1 Corticosteroids and intravenous immune globulin (IVIG) are the most commonly used first-line treatments; splenectomy, rituximab, and thrombopoietin receptor agonists (TPO-RAs) are all acceptable second-line options.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent estimates from US health care claims databases (2010-2016) found an annual incidence of ITP of 6.1 per 100 000 people. 1 New ITP diagnoses occur in nearly 20 000 children and adults each year in the United States, with collective medical care costs of more than $400 million within the first 12 months after diagnosis. 1 Corticosteroids and intravenous immune globulin (IVIG) are the most commonly used first-line treatments; splenectomy, rituximab, and thrombopoietin receptor agonists (TPO-RAs) are all acceptable second-line options.…”
Section: Introductionmentioning
confidence: 99%
“…1 New ITP diagnoses occur in nearly 20 000 children and adults each year in the United States, with collective medical care costs of more than $400 million within the first 12 months after diagnosis. 1 Corticosteroids and intravenous immune globulin (IVIG) are the most commonly used first-line treatments; splenectomy, rituximab, and thrombopoietin receptor agonists (TPO-RAs) are all acceptable second-line options. 2,3 TPO-RAs, including eltrombopag, romiplostim, and avatrombopag, now provide an alternative option among patients for whom second-line therapy is indicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to population-based pediatric studies in other countries, the prevalence in this study was higher than in the USA (4.1–13.6 per 100,000 persons). 5,10 The incidence was also higher than in USA and western countries (2.8–8.8 per 100,000 persons), 8,11,15 and in Asian country, Taiwan (4.0 per 100,000 persons). 6 An earlier Korean study showed similar results (14.3 per 100,000 persons).…”
Section: Discussionmentioning
confidence: 84%
“…Although previous nationwide population-based or cohort studies of ITP demonstrated higher rates in children than adults, ITP data was often only reported on indirectly as a subset of adult ITP epidemiological data, and categorized by age based on 5- or 10-year intervals. 512…”
Section: Introductionmentioning
confidence: 99%